1998
DOI: 10.1017/s1355838298980207
|View full text |Cite
|
Sign up to set email alerts
|

Base pairing with U6atac snRNA is required for 5′ splice site activation of U12-dependent introns in vivo

Abstract: The minor U12-dependent class of eukaryotic nuclear pre-mRNA introns is spliced by a distinct spliceosomal mechanism that requires the function of U11, U12, U5, U4atac, and U6atac snRNAs. Previous work has shown that U11 snRNA plays a role similar to U1 snRNA in the major class spliceosome by base pairing to the conserved 59 splice site sequence. Here we show that U6atac snRNA also base pairs to the 59 splice site in a manner analogous to that of U6 snRNA in the major class spliceosome. We show that splicing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 33 publications
3
73
0
Order By: Relevance
“…Comparison of the intramolecular stem-loop structures of various U6 and U6atac snRNAs+ The sequences are from human, A. thaliana (plant), and Saccharomyces cerevisiae (yeast)+ In each case the putative helix Ib interactions with the conspecific U2 or U12 snRNAs are shown below the intramolecular structures+ The boxed sequences are those that were substituted into the human U6atac snRNA in our previous analysis of the plant U6atac stem-loop (Shukla & Padgett, 1999) or in the work discussed here+ analysis has shown that this cryptic splicing reaction is catalyzed by the U2-dependent spliceosome (Tarn & Steitz, 1996a)+ Cotransfection of U6atac and U11 snRNA expression constructs that contain the compensatory mutations shown in Figure 1B restores U12-dependent splicing at the normal 59 and 39 splice sites to nearly wild-type levels+ This suppression is completely dependent on the U6atac suppressor while the U11 suppressor improves the level of suppression (Incorvaia & Padgett, 1998)+ This dependence on the addition of an exogenous suppressor U6atac allows us to assay the in vivo effects of mutations at other sites in U6atac snRNA+…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Comparison of the intramolecular stem-loop structures of various U6 and U6atac snRNAs+ The sequences are from human, A. thaliana (plant), and Saccharomyces cerevisiae (yeast)+ In each case the putative helix Ib interactions with the conspecific U2 or U12 snRNAs are shown below the intramolecular structures+ The boxed sequences are those that were substituted into the human U6atac snRNA in our previous analysis of the plant U6atac stem-loop (Shukla & Padgett, 1999) or in the work discussed here+ analysis has shown that this cryptic splicing reaction is catalyzed by the U2-dependent spliceosome (Tarn & Steitz, 1996a)+ Cotransfection of U6atac and U11 snRNA expression constructs that contain the compensatory mutations shown in Figure 1B restores U12-dependent splicing at the normal 59 and 39 splice sites to nearly wild-type levels+ This suppression is completely dependent on the U6atac suppressor while the U11 suppressor improves the level of suppression (Incorvaia & Padgett, 1998)+ This dependence on the addition of an exogenous suppressor U6atac allows us to assay the in vivo effects of mutations at other sites in U6atac snRNA+…”
Section: Resultsmentioning
confidence: 78%
“…We have previously developed an in vivo mutational suppressor assay for the function of several of the snRNAs involved in U12-dependent splicing (Hall & Padgett, 1996;Kolossova & Padgett, 1997;Incorvaia & Padgett, 1998;Shukla & Padgett, 1999)+ This assay relies on the genetic suppression of splicing defects due to splice site mutations in a U12-dependent intron by coexpression of compensatory mutant snRNAs+ For U6atac snRNA, a mutation in the 59 splice site of a transfected minigene construct, which blocks splicing at the normal sites, is suppressed by cotransfection of expression constructs containing compensatory mutations in U11 and U6atac snRNAs+ The elements of this assay are diagramed in Figure 1B+ The P120 minigene contains a double mutation in positions 5 and 6 of the 59 splice site of the U12-dependent intron F (P120 CC5/ 6GG)+ This mutation causes a complete loss of splicing activity at the normal 59 and 39 splice sites and the concomitant activation of a pair of cryptic splice sites within the intron (Kolossova & Padgett, 1997)+ In vitro FIGURE 2. Comparison of the intramolecular stem-loop structures of various U6 and U6atac snRNAs+ The sequences are from human, A. thaliana (plant), and Saccharomyces cerevisiae (yeast)+ In each case the putative helix Ib interactions with the conspecific U2 or U12 snRNAs are shown below the intramolecular structures+ The boxed sequences are those that were substituted into the human U6atac snRNA in our previous analysis of the plant U6atac stem-loop (Shukla & Padgett, 1999) or in the work discussed here+ analysis has shown that this cryptic splicing reaction is catalyzed by the U2-dependent spliceosome (Tarn & Steitz, 1996a)+ Cotransfection of U6atac and U11 snRNA expression constructs that contain the compensatory mutations shown in Figure 1B restores U12-dependent splicing at the normal 59 and 39 splice sites to nearly wild-type levels+ This suppression is completely dependent on the U6atac suppressor while the U11 suppressor improves the level of suppression (Incorvaia & Padgett, 1998)+ This dependence on the addition of an exogenous suppressor U6atac allows us to assay the in vivo effects of mutations at other sites in U6atac snRNA+…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The discovery that certain RNA species possess catalytic activity has generated significant interest in the potential therapeutic use of catalytic RNA molecules (ribozymes) in controlling gene expression (for a review, see Christoffersen & Marr, 1995)+ Ribozymes have been shown to function in trans and can be directed against foreign target sequences by flanking the catalytic core with sequences complementary to the target (Uhlenbeck, 1987;Haseloff & Gerlach, 1988)+ The hammerhead is the smallest of the known ribozyme motifs and therefore amenable to experimental manipulation (for a review, see Symons, 1992)+ Hammerhead ribozymes have broad potential as therapeutic agents for the selective control of gene expression (for a review, see Haseloff & Gerlach, 1988;Sarver et al+, 1990;Christoffersen & Marr, 1995)+ An important problem confronting the use of hammerhead ribozymes as therapeutic agents is that of maximizing the interaction of ribozymes to their target RNAs in vivo+ Experiments employing the unique property of retroviruses to dimerize prior to and during packaging have provided a paradigm for ribozyme-target colocalization (Sullenger & Cech, 1993;Pal et al+, 1998)+ The dimerization and packaging of retroviral RNAs creates a unique physical association of two genomic RNAs+ When a ribozyme is tethered to the dimerization domain, the physical interaction of two dimerization sequences facilitates the base pairing of ribozyme to target+ Physical associations of nonviral RNAs occur within cells, but these usually involve specific base pairing interactions such as snRNAs with splicing signals (Wu & Manley, 1991;Sun & Manley, 1995;Incorvaia & Padgett, 1998)+ The interaction of U1 snRNA with the 59 splice signal has been used as an approach for colocalization of a ribozyme with an HIV target (Michienzi et al+, 1998)+ More subtle methods for ribozyme-target colocalization can take advantage of the properties of some messenger RNAs to be localized within specific subcellular compartments+ The first evidence for cytoplasmic mRNA localization came from the observation that actin tran-scripts are unevenly distributed in ascidian embryos (Jeffery et al+, 1983)+ Subsequently, several maternal mRNAs were identified in Xenopus (Melton, 1987) and Drosophila (Frigerio et al+, 1986) that are localized during oogenesis, and many mRNAs are localized in neurons (Garner et al+, 1988;Burgin et al+, 1990;Tiedge et al+, 1991) and oligodendrocytes (Ainger et al+, 1993)+ Localized mRNAs have also been discovered in somatic cells …”
Section: Introductionmentioning
confidence: 99%